A Comparative study for striatal-direct and -indirect pathway neurons to DA depletion-induced lesion in a PD rat model. (September 2018) - Zheng, Xuefeng; Wu, Jiajia; Zhu, Yaofeng; Chen, Si; Chen, Zhi; Chen, Tao; Huang, Ziyun; Wei, Jiayou; Li, Yanmei; Lei, Wanlong
Abstract: Striatal-direct and -indirect Pathway Neurons showed different vulnerability in basal ganglia disorders. Therefore, present study aimed to examine and compare characteristic changes of densities, protein and mRNA levels of soma, dendrites, and spines between striatal-direct and -indirect pathway neurons after DA depletion by using immunohistochemistry, Western blotting, real-time PCR and immunoelectron microscopy techniques. Experimental results showed that: 1) 6OHDA-induced DA depletion decreased the soma density of striatal-direct pathway neurons (SP+), but no significant changes for striatal-indirect pathway neurons (ENK+). 2) DA depletion resulted in a decline of dendrite density for both striatal-direct (D1+) and -indirect (D2+) pathway neurons, and D2+ dendritic density declined more obviously. At the ultrastructure level, the densities of D1+ and D2+ dendritic spines reduced in the 6OHDA groups compared with their control groups, but the density of D2+ dendritic spines reduced more significant than that of D1. 3) Striatal DA depletion down-regulated protein and mRNA expression levels of SP and D1, on the contrary, ENK and D2 protein and mRNA levels of indirect pathway neurons were up-regulated significantly. Present results suggested that indirect pathway neurons be more sensitive to 6OHDA-induced DA depletion. Highlights: Striato-indirect pathway neurons were more sensitive to 6OHDA-induced DA depletion. DA depletion decreased the soma density of striatal-direct pathway neurons. D2+ dendritic and spine density decreased more obviously than D1+ after DA depletion. Striatal DA depletion down-regulated protein and mRNA expression levels of SP and D1. Striatal DA depletion up-regulated protein and mRNA expression levels of ENK and D2.